Assessing the Impact of IT Competency on Organizational Learning Capability of Indonesian Manufacturing Firms - Alizar Hasan (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2010)
This paper attempt to assessing the impact of IT competency on organizational learning capability by using the measurement scale that have been developed by Tippins et al. and Gomes et al. These studies cover a sample of 192 manufacturing firms. IT competencies are classified into three dimensions: IT knowledge, IT operations, and IT objects, and organizational learning capability are classified into four dimensions: Managerial commitment, System perspec-tive, Openness and experimentation, and Knowledge transfer and integration. The result of factor analysis on IT competency and Organizational learning capability show that all items have high loading only on a single factor with ranging from .60 to .84. The findings revealed that IT competency positively and significantly influences the organizational learning capability of Indonesian manufacturing firms.